1996
DOI: 10.1159/000189319
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutarate Application in Hemodialysis Patients Improves Amino Acid Metabolism

Abstract: In hemodialysis patients, free amino acids and α-ketoacids in plasma were determined by fluorescence HPLC to assess the effect of α-ketoglutarate administration in combination with the phosphate binder calcium carbonate on the amino acid metabolism. During 1 year of therapy in parallel to inorganic phosphate, urea in plasma decreased significantly, histidine, arginine and proline as well as branched chain α-ketoacids, in particular α-ketoisocaproate, a regulator of protein metabolism, increased. Thus, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…We presumed that the chronic dialyzed patients receiving keto acids should have a protein intake of at least 0.8 g/kg/day. One possible reason for keeping stable nutritional status may be related to the keto acid supplementation, which provided the essential amino acids and their corresponding keto acids, and thus decreased the degradation of branched-chain amino acids while increasing the essential amino acids, which may lead to stimulation of protein synthesis and reduction in protein degradation [20]. Keto acids raise the cycling utilization of urea nitrogen in the body to synthesize essential amino acids, which corrects negative nitrogen balance and improves the protein nutrition status [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presumed that the chronic dialyzed patients receiving keto acids should have a protein intake of at least 0.8 g/kg/day. One possible reason for keeping stable nutritional status may be related to the keto acid supplementation, which provided the essential amino acids and their corresponding keto acids, and thus decreased the degradation of branched-chain amino acids while increasing the essential amino acids, which may lead to stimulation of protein synthesis and reduction in protein degradation [20]. Keto acids raise the cycling utilization of urea nitrogen in the body to synthesize essential amino acids, which corrects negative nitrogen balance and improves the protein nutrition status [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A highly significant correlation has been observed between protein and phosphate intake [19]. The serum phosphorus level can certainly be reduced by a low-protein diet (LPD), and if the diet is supplemented with keto acids, which is a potent phosphate binder, the serum phosphorus level can be further reduced [20]. As early as 1988, Schaefer et al [21] have demonstrated the beneficial effects of LPD and keto acid supplementation on serum phosphorus and parathyroid hormone levels in uremic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note is the extensive oxidation of α-KG by enterocytes that may suppress GLN catabolism and ammonia production by intestinal cells (Yao et al 2012). The adverse side effect of α-KG administration may be catabolism of BCAA as demonstrated by increased levels of branched-chain keto acids in hemodialysis patients (Riedel et al 1996). …”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Unlike free Gln, AKG has a good water solubility, is non-toxic and relatively stable in water solutions, and thus represents an effective alternative Gln source for the composition of parenteral solutions (Filip and Pierzynowski, 2007). In addition, AKG can prevent uncontrolled nitrogen (N) loss from muscle protein in human patients suffering from post-surgical trauma, burns or chronic malnutrition, controlling the amino acid (AA) blood profile and reducing the blood urea in patients undergoing hemodialysis (Blomqvist et al, 1995;Riedel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%